Some questions of legal regulation of the information security in Kazakhstan. Қазақстанда ақпараттарды қорғаудың құқықтық реттеудің кейбір сұрақтары. - S. Tynybekov.; R. Erezhepkyzy. (Хабаршы. Заң сериясы, 2016)
The right of access to official information is really important. The constitution of RK fixes guarantees of realization of the right of citizens to information, based on the fact that the right to information is a fundamental human right. At the same time, the current law is not fully possible to implement this law. Ресми ақпаратқа қол жетілімділік құқығы аса маңызды. ҚР Конституциясы азаматардың ақпарат алуға құқылы екеніне кепілдік береді. Сонымен қатар, қолданыстағы заңнамада ол құқықтың іске асырылуы толық қамтамасыз етілмеген.